Comparison and Subjective Evaluation of Safety and Efficacy of Antihypertensive Drugs from the Group Angiotensin-Converting Enzyme and Diuretics (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: Cardiovascular diseases are a very significant sociomedical problem in all countries of the world. Proper therapy of cardiovascular diseases, as well as their timely prevention, is one of the most important conditions for increasing life expectancy and maintaining quality of life. One of the most effective ways to achieve this goal is the timely detection and proper treatment of hypertension. Doctors note that in diseases such as stroke, coronary heart disease, including myocardial infarction, and heart and kidney failure, their level may be reduced as a result of adequate antihypertensive therapy. This is especially important for Ukraine, where the incidence of cardiovascular disease is increasing every year. Recently, along with the expansion of opportunities in the treatment of hypertension, there is enough information about the effectiveness of drugs that lower blood pressure. Materials and Methods: Methods such as questionnaires of patients (content analysis of case histories) were used. Data processing was performed using statistical and mathematical methods and graphical analysis. Results: There were some patterns of lowering blood pressure in patients on the background of monotherapy of hypertension and patients following the doctor’s instructions for treatment. Discussion and Conclusion: As a result of the study, it was found that most patients follow the recommendations of doctors on the appointment of antihypertensive drugs.